PENGATURAN TENTANG LIMBAH CAIR BAHAN BERACUN DAN BERBAHAYA MENURUT UNDANG-UNDANG NO. 32 TAHUN 2009 TENTANG PERLINDUNGAN DAN PENGELOLAAN LINGKUNGAN HIDUP - Bayu Saksono (Journal of Law ( Jurnal Ilmu Hukum ), 2021)
AbstractThe development of workshop business activities mostly occurs in big cities, including Samarinda City. The workshop's business activities have positive and negative impacts. The positive impact is that it contributes to Local Original Revenue (PAD), provides welfare, and also provides employment opportunities. Expected, activities that involve consideration, soil pollution, air pollution, air pollution, or health improvement. In addition, more serious environmental problems can be caused by hazardous waste and the results of translation (B3) consisting of used oil, hereinafter referred to as used lubricating oil as a result of the workshop business activities. The lubricating oil produced is inherent specifically in Article 12 paragraph (1) of Government Regulation No. 101 Concerning Management of Hazardous and Toxic Waste that reads: "Everyone who produces B3 Waste must carry out B3 Waste Storage". B3 is not in accordance with Government Regulation No. 101 About the Management of Hazardous and Toxic Waste Material will greatly protect the surrounding environment